Problems with the use of habitat methods for the development of a hydrological formula allowing the determination of the environmental flow - Paweł Madej; Jerzy Grela (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of the article is to discuss the idea of using the biotic classification of watercourses and habitat methods to develop simplified hydrological formulas, enabling the determination of environmental flows. Adjustment of such a solution to the hydrological regime of watercourses and the practical possibilities of implementing the formulas are investigated.